Towards an inclusive sufficiency narrative - Korjonen‐Kuusipuro, Kristiina; Koskimäki, Teemu; Wojciechowski, Adam; Neuvonen, Aleksi (Human Technology, 2024)
In this Editorial, we tackle perhaps the most urgent issue of our time – the need to orient lives more towards sufficiency. Achieving such a transformation also requires a parallel paradigm shift in science. In this Editorial, we have two guest authors, Teemu Koskimäki and Aleksi Neuvonen, who are members of the SISU Consortium doing research on sufficiency transition in Finland.